Electrophoretic Deposition of Chitosan/h-BN and Chitosan/h-BN/TiO2 Composite Coatings on Stainless Steel (316L) Substrates - Namir S. Raddaha (Materials, 2014)
This article presents the results of an experimental investigation designed to deposit chitosan/hexagonal boron nitride (h-BN) and chitosan/h-BN/titania (TiO2) composites on SS316L substrates using electrophoretic deposition (EPD) for potential antibacterial applications. The influence of EPD parameters (voltage and deposition time) and relative concentrations of chitosan, h-BN and TiO2 in suspension on deposition yield was studied. The composition and structure of deposited coatings were investigated by FTIR, XRD and SEM. It was observed that h-BN and TiO2 particles were dispersed in the chitosan matrix through simultaneous deposition. The adhesion between the electrophoretic coatings and the stainless steel substrates was tested by using tape test technique, and the results showed that the adhesion strength corresponded to 3B and 4B classes. Corrosion resistance was evaluated by electrochemical polarization curves, indicating enhanced corrosion resistance of the chitosan/h-BN/TiO2 and chitosan/h-BN coatings compared to the bare stainless steel substrate. In order to investigate the in-vitro inorganic bioactivity, coatings were immersed in simulated body fluid (SBF) for 28 days. FTIR and XRD results showed no formation of hydroxyapatite on the surface of chitosan/h-BN/TiO2 and chitosan/h-BN coatings, which are therefore non bioactive but potentially useful as antibacterial coatings.